PENGKAJIAN METODA PELAPISAN ULANG CAMPURAN BERASPAL DIATAS PERKERASAN BETON - Neni Kusnianti; Y. Ronny P.A (Jurnal Jalan-Jembatan, 2006)
As a normal condition of pavement, rigid pavement performance will decrease as a result of traffic load and environment factors. Generally, the decrease of performance may in term of structural or functionality of pavement to support traffic. To improve pavement performance and make the most of existing pavement effectively some efforts are needed to reinforce the existing pavement. Service life of rigid pavement can be extended by overlaying new asphalt layer above the existing rigid pavement. Overlay flexible pavement above rigid pavement need a guidance, so that the expected service life can meet the design and also the existing rigid pavement strength can be used effectively and efficiently. In this paper some method of AC overlay over rigid pavement are presented such as Austroad and AASHTO method.